Protecting 90 million refugees on climate crisis frontlines - Laderach, Peter; Craparo, Alessandro (2025)
Alliance Bioversity –CIAT researchers—as part of the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM)—provided key evidence for UNHCR’s groundbreaking report on conflict, climate, and displacement. Providing clear evidence that more than 90 million refugees and forcibly displaced people are exposed to climate-related hazards has empowered UNHCR to reinforce its advocacy. The UN agency urges climate negotiators, funders, and policymakers to protect these most vulnerable populations.